1980
DOI: 10.1507/endocrj1954.27.239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of electrochemical stimulation of the medial preoptic area and the hypothalamic arcuate nucleus upon LH release in ovariectomized and proestrous rats.

Abstract: The effect of electrochemical stimulation of the medial preoptic area (MPO) and the hypothalamic arcuate nucleus (ARC) on LH release was compared among longterm ovariectomized (OVX), ovariectomized rats treated with estradiol benzoate (OVX-F) and proestrous (PE) rats under pentobarbital anesthesia.The MPO stimulation failed to facilitate LH release in OVX rats whereas the stimulation increased serum LH levels in both OVX-E and PE rats. The ARC stimulation resulted in an elevation of serum LH in OVX and PE rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is not clear in rats whether the rhythm origi nates from the medial basal hypothalamus or not, but the ARC contains high levels of LH-RH [6] and electrochemi cal stimulation of the ARC induces a rapid increase in se rum LH, though MPO stimulation fails to facilitate LH re lease in ovariectomized rats [10]. The findings of Séiâlô et al [15] revealed that no LH-RH positive cell bodies could be seen in the ARC though numerous LH-RH positive fi bers passed through the ARC in rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear in rats whether the rhythm origi nates from the medial basal hypothalamus or not, but the ARC contains high levels of LH-RH [6] and electrochemi cal stimulation of the ARC induces a rapid increase in se rum LH, though MPO stimulation fails to facilitate LH re lease in ovariectomized rats [10]. The findings of Séiâlô et al [15] revealed that no LH-RH positive cell bodies could be seen in the ARC though numerous LH-RH positive fi bers passed through the ARC in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The increased amplitude of a single LH pulse was observed in intact rats following longer immobili zation stress [unpubl. observations], electrical stimulation of the brain in rats [15], or after the suppression of LH re lease by estrogen or neurotransmitter blockers in ovariec tomized monkeys [3,37]. Increased amplitude and duration of LH pulses following the period of inhibition appeared in intact animals, but in the rats lacking some component which regulate the pulsatile release of anterior pituitary hor mone as the animals with a small anterior cut, might exhibit greater pulses of hormone release without inhibitory period.…”
Section: Discussionmentioning
confidence: 99%